+0  
 
0
497
5
avatar

sqrt(8-sqrt(55))+sqrt(8+sqrt(55))

Guest Jan 25, 2015

Best Answer 

 #3
avatar+19632 
+10

sqrt(8-sqrt(55))+sqrt(8+sqrt(55))

$$\sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}} \quad | \quad \sqrt{ x^2 } \\ \\
= \sqrt{ \left( \sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}} \right)^2 } \\ \\
= \sqrt{ (8-\sqrt{55}) +(8+ \sqrt{55}) +2*\left( \sqrt{8-\sqrt{55}} \right)* \left(\sqrt{8+\sqrt{55}} \right)} \\ \\
= \sqrt{ 16+2*\left( \sqrt{8-\sqrt{55}} \right) * \left(\sqrt{8+\sqrt{55}} \right) } \\ \\
= \sqrt{ 16+2* \sqrt{8^2- 55 } }\\ \\
= \sqrt{ 16+2* \sqrt{64-55} } \\ \\
= \sqrt{ 16+2* \sqrt{9} } \\ \\
= \sqrt{ 16+2* 3 }\\ \\
= \sqrt{ 22 }\\ \\
= 4.69041576$$

heureka  Jan 25, 2015
 #1
avatar+92781 
+10

$$\sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}}$$

 

This is a tough one!

First I am going to consider      $$8-\sqrt{55}$$

I want to express this as a perfect square.

$$\\8-\sqrt{55}\\\\
=\frac{5}{2}-\sqrt{55}+\frac{11}{2}\\\\
=\frac{25}{10}-\frac{10\sqrt{55}}{10}+\frac{55}{10}\\\\
=\frac{25-10\sqrt{55}+55}{10}\\\\
=\frac{5^2-10\sqrt{55}+(\sqrt{55})^2}{10}\\\\
=\frac{(5-\sqrt{55})^2}{10}\\\\
But\;\; (5-\sqrt{55})^2=(\sqrt{55}-5)^2\;\;$and I want the positive one, so $\\\\
=\frac{(\sqrt{55}-5)^2}{10}\\\\$$

 

$$\\Hence\\\\
\sqrt{8-\sqrt{55}}\\\\
=\sqrt{\frac{(\sqrt{55}-5)^2}{10}}\\\\
=\frac{\sqrt{55}-5}{\sqrt{10}}}\\\\
=\frac{\sqrt{10*55}-5\sqrt{10}}{10}\\\\
=\frac{\sqrt{2*5*5*11}-5\sqrt{10}}{10}\\\\
=\frac{5\sqrt{22}-5\sqrt{10}}{10}\\\\
=\frac{\sqrt{22}-\sqrt{10}}{2}\\\\$$

 

NOW, BY THE SAME LOGIC,

 

$$\\Hence\\\\
\sqrt{8}+\sqrt{55}=\frac{\sqrt{22}+\sqrt{10}}{2}\\\\
SO\\\\
\sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}}\\\\
=\frac{\sqrt{22}-\sqrt{10}}{2}+\frac{\sqrt{22}+\sqrt{10}}{2}\\\\
=\frac{2\sqrt{22}}{2}\\\\
=\sqrt{22}\\\\$$

Melody  Jan 25, 2015
 #2
avatar+87301 
0

Very crafty, Melody....!!!

 

CPhill  Jan 25, 2015
 #3
avatar+19632 
+10
Best Answer

sqrt(8-sqrt(55))+sqrt(8+sqrt(55))

$$\sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}} \quad | \quad \sqrt{ x^2 } \\ \\
= \sqrt{ \left( \sqrt{8-\sqrt{55}}+\sqrt{8+\sqrt{55}} \right)^2 } \\ \\
= \sqrt{ (8-\sqrt{55}) +(8+ \sqrt{55}) +2*\left( \sqrt{8-\sqrt{55}} \right)* \left(\sqrt{8+\sqrt{55}} \right)} \\ \\
= \sqrt{ 16+2*\left( \sqrt{8-\sqrt{55}} \right) * \left(\sqrt{8+\sqrt{55}} \right) } \\ \\
= \sqrt{ 16+2* \sqrt{8^2- 55 } }\\ \\
= \sqrt{ 16+2* \sqrt{64-55} } \\ \\
= \sqrt{ 16+2* \sqrt{9} } \\ \\
= \sqrt{ 16+2* 3 }\\ \\
= \sqrt{ 22 }\\ \\
= 4.69041576$$

heureka  Jan 25, 2015
 #4
avatar+87301 
0

Also well done, heureka...!!!

Your method is a little more intuitive to me, than Melody's.....

But.......either one gets the job done!!!

CPhill  Jan 25, 2015
 #5
avatar+92781 
0

Thanks Chris,  

Yes, I will admit, I like Heureka's method better too.   

Melody  Jan 25, 2015

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.